2014
DOI: 10.1016/j.biomaterials.2014.05.044
|View full text |Cite
|
Sign up to set email alerts
|

The use of bi-layer silk fibroin scaffolds and small intestinal submucosa matrices to support bladder tissue regeneration in a rat model of spinal cord injury

Abstract: Adverse side-effects associated with enterocystoplasty for neurogenic bladder reconstruction have spawned the need for the development of alternative graft substitutes. Bi-layer silk fibroin (SF) scaffolds and small intestinal submucosa (SIS) matrices were investigated for their ability to support bladder tissue regeneration and function in a rat model of spinal cord injury (SCI). Bladder augmentation was performed with each scaffold configuration in SCI animals for 10 wk of implantation and compared to non-au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 31 publications
0
43
0
Order By: Relevance
“…Histomorphometric analyses (N=3–11 animals per group) were performed as previously described [37, 38] to assess the degree of constructive tissue remodeling in both control and implant groups using ImageJ software (version 1.47). Image thresholding and area measurements were carried out on 8 independent microscopic fields (magnification 20X) equally dispersed along the periphery and central regions of the original surgical sites to determine the percentage of stained tissue area occupied by MY32+ skeletal muscle bundles, α-SMA+ smooth muscle bundles and CK+ epithelia relative to the total field area examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histomorphometric analyses (N=3–11 animals per group) were performed as previously described [37, 38] to assess the degree of constructive tissue remodeling in both control and implant groups using ImageJ software (version 1.47). Image thresholding and area measurements were carried out on 8 independent microscopic fields (magnification 20X) equally dispersed along the periphery and central regions of the original surgical sites to determine the percentage of stained tissue area occupied by MY32+ skeletal muscle bundles, α-SMA+ smooth muscle bundles and CK+ epithelia relative to the total field area examined.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro biocompatibility studies have shown the propensity of these biomaterials to support attachment, proliferation, and differentiation of esophageal cell lines; key cellular processes involved in promoting host tissue integration and functional maturation of regenerating tissue [36]. Previous reports from our group have demonstrated the utility of bi-layer SF scaffolds to promote constructive tissue remodeling within the urinary bladder [34, 35, 37] and the urethra [38], however their potential for esophageal tissue repair is unknown. In the present study, we investigated the efficacy of these scaffolds to support functional tissue regeneration in a rat model of onlay esophagoplasty.…”
Section: Introductionmentioning
confidence: 99%
“…In a rat model of neurogenic bladder induced by spinal cord injury, Obara’s group indicated that ABM promoted host integration of smooth muscle and urothelial cells throughout the grafted area [50] while studies by Urakami demonstrated that voiding function could be improved following ABM implantation [51]. Recent data from our laboratory has also shown that acellular SIS matrices undergo remodeling and facilitate ingrowth of vascularized smooth muscle as well as urothelial cells throughout implantation sites in the setting of neuropathogenic bladder disease [52]. …”
Section: Properties and Performance Of Tissue Engineered Constructmentioning
confidence: 99%
“…Our results have shown the feasibility of the bi-layer silk fibroin scaffold to support regeneration of innervated, vascularized smooth muscle and urothelial tissues with structural, mechanical, and functional properties comparable to non-augmented controls in a non-diseased porcine model of bladder repair [61]. Recent work from laboratory has also detailed the ability of bi-layer silk fibroin scaffolds to promote de novo bladder tissue formation and mitigation of high intravesical pressures encountered in rat model of neurogenic bladder [52]. Further validation of silk fibroin biomaterials for augmentation cystoplasty in large animal models of bladder disease is necessary before clinical translation is considered.…”
Section: Properties and Performance Of Tissue Engineered Constructmentioning
confidence: 99%
“…Though out of the true synthetic biomaterials field,"silk fibroin"made scaffolds, coated with ECM proteins, have been timely used, in animal model bladder tissue engineering, as templates for urothelial/smooth muscle cell seeding procedure, thus achieving a construct endowed with effective structural and functional proper such as particularly biodegradability, plasticity, compliance (42,43). In this regard, recent animal model studies have shown that the stretched electrospun silk fibroin matrix implantation can strongly promote bladder tissue regeneration with proper structure/function features, in comparison with BAM (44).…”
Section: Regenerative Medicine and Tissue Engineering Research Develomentioning
confidence: 99%